Predictors of Industry 4.0 technologies affecting logistic enterprises’ performance: international perspective from economic lens - Ślusarczyk, Beata; Tvaronavičienė, Manuela; Ul Haque, Adnan; Oláh, Judit (Technological and Economic Development of Economy, 2020)
This study examines the influence of the fourth industrial revolution on global and national economies by considering the case of Hungary, Canada and Poland. The research compares local logistic business to gain insight about the implementation of Industry 4.0 practices through exploring existing limited knowledge, preparing staff for challenges, implementation barriers, recognizing potentials and implications of Industry 4.0. Using mixed sampling strategies, we gathered data from 180 logistic enterprises (60 each in considered economies) and established the multi-predictors to investigate the relationship between Industry 4.0 technologies and performance of enterprises. Results revealed that all considered predictors are statistically significant in affecting the impact of Industry 4.0 technologies on the performance of enterprises in all three economies. However, the magnitude of impact differs to some extent. The authors propose recommendations for implications of Industry 4.0 technologies. First published online 22 September 2020